Preparation of Y3Al5O12 Phosphor by Impinging Streams Homogeneous Precipitation-Molten Salt Assisted Method - Ge1, Xizhen; Lin1, Qiang; Gu1, Chunxiu; Zhu1, Yan; Jiang1, Nan; Zhao1, Bingbing; Wang1, Meng; Tian2, Pingfang (Asian Journal of Chemistry, 2012)
Fine and spherical Y3Al5O12 (YAG) phosphor was synthesized by firing a preparative precursor with the molten salts of Na2SO4, S and K2SO4. The precursor was obtained by impinging streams homogeneous precipitation of yttrium and aluminum with ammonia water (AW) as precipitant. The experimental results show that the precursor transforms to YAG at about 700 ºC using molten-calcination method. Compared with the solid-state reaction method and impinging streams homogeneous precipitation-direct calcination method, the YAG phase transition temperature with the present method can be decreased about 800 and 200 ºC, respectively. The prepared YAG phosphor is of spherical structure with 200-300 nm by molten-calcination at 1000 ºC for 2 h and has better crystallinity and more regularly spherical morphology than that from direct-calcination method.